Evaluation of the Talaqqi Method at Daarul Ulum Al-Hadi Islamic Boarding School in Kota Besi, East Waringin City - Nur Aisyah; Zainap Hartati; Saiful Lutfi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to evaluate the implementation of the talaqqi method in the memorization of the Qur'an at Pondok Pesantren Daarul Ulum Al-Hadi Kota Besi, Kota Waringin Timur using the CIPP (Context, Input, Process, Product) evaluation model. This qualitative descriptive study employed data collection techniques through observation, interviews, and documentation. The results show that the talaqqi method is effective in improving the memorization skills of the female students (santriwati). However, several challenges were identified during its implementation, such as varying memorization abilities among students, limited numbers of teachers, and a lack of variation in the teaching methods used. Evaluation of the product aspect indicates that there has been an improvement in the number of memorized verses, though further enhancement is needed in the areas of tajwid (pronunciation) and makharajul huruf (articulation of letters). Therefore, this study recommends that the pesantren increase the number of teachers, diversify teaching methods, and develop a more comprehensive evaluation system to improve the overall quality of Qur'anic memorization among the santriwati. This research contributes to the development of more effective methods in Qur'anic memorization in pesantren environments.